2018
DOI: 10.1093/nar/gky1277
|View full text |Cite
|
Sign up to set email alerts
|

The effect of macromolecular crowding on single-round transcription byEscherichia coliRNA polymerase

Abstract: Previous works have reported significant effects of macromolecular crowding on the structure and behavior of biomolecules. The crowded intracellular environment, in contrast to in vitro buffer solutions, likely imparts similar effects on biomolecules. The enzyme serving as the gatekeeper for the genome, RNA polymerase (RNAP), is among the most regulated enzymes. Although it was previously demonstrated that macromolecular crowding affects association of RNAP to DNA, not much is known about how crowding acts on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 54 publications
0
31
0
Order By: Relevance
“…Considering the low probe binding rate in the experiment, the start points of the transcription signal in Fig. 4c, d likely do not indicate the start of transcription, rather 54 the binding of the fastFISH probe after the transcription has already started. On the other hand, the Alexa 488 bleaching time (the 99% confidence level: 17.7 ± 12.4 s, Supplementary Fig.…”
Section: D-smartmentioning
confidence: 95%
See 1 more Smart Citation
“…Considering the low probe binding rate in the experiment, the start points of the transcription signal in Fig. 4c, d likely do not indicate the start of transcription, rather 54 the binding of the fastFISH probe after the transcription has already started. On the other hand, the Alexa 488 bleaching time (the 99% confidence level: 17.7 ± 12.4 s, Supplementary Fig.…”
Section: D-smartmentioning
confidence: 95%
“…The probe DNA concentration was kept low (200 pM) to reduce fluorescence background, resulting in a low transcription detection rate in these experiments (6 of 628 trajectories) since hybridization rate is only 1.2 × 10 −3 s −1 without the presence of glycerol. Moreover, the presence of glycerol will further decrease the hybridization kinetics 54,55 . Considering the low probe binding rate in the experiment, the start points of the transcription signal in Fig.…”
Section: D-smartmentioning
confidence: 99%
“…This volume exclusion affects various enzymatic reactions, either by increasing or decreasing their rates, depending on the change in size of the reactants [114][115][116][117]. While it has been shown that macromolecular crowding demonstrates mostly advantageous effects on cell metabolism [114,[117][118][119], it can also function as a constraint for cells which exhibit high metabolic rates [120]. Beg et al [121] developed a flux balance model of E. coli (FBAwMC), including a constraint for the enzyme concentrations, considering the macromolecular crowding.…”
Section: Short-term Uptake Dynamicsmentioning
confidence: 99%
“…This volume exclusion affects various enzymatic reactions, either by increasing or decreasing their rates, depending on the change in size of the reactants [124127]. While it has been shown that macromolecular crowding demonstrates mostly advantageous effects on cell metabolism [124, 127129], it can also function as a constraint for cells which exhibit high metabolic rates [130]. Beg QK , et al [131] developed a flux balance model of E.coli (FBAwMC), including a constraint for the enzyme concentrations, considering the macromolecular crowding.…”
Section: Discussionmentioning
confidence: 99%